The effect of dead elements on the accuracy of Doppler ultrasound measurements - Vachutka, Jaromir; Dolezal, Ladislav; Kollmann, Christian; Klein, Jakob (Ultrasonic imaging, 2014)
The objective of this study is to investigate the effect of multiple dead elements in an ultrasound probe on the accuracy of Doppler ultrasound measurements. For this work, we used a specially designed ultrasound imaging system, the Ultrasonix Sonix RP, that provides the user with the ability to disable selected elements in the probe. Using fully functional convex, linear, and phased array probes, we established a performance baseline by measuring the parameters of a laminar parabolic flow profile. These same parameters were then measured using probes with 1 to 10 disabled elements. The acquired velocity spectra from the functional probes and the probes with disabled elements were then analyzed to determine the overall Doppler power, maximum flow velocity, and average flow velocity. Color Flow Doppler images were also evaluated in a similar manner. The analysis of the Doppler spectra indicates that the overall Doppler power as well as the detected maximum and average velocities decrease with the increasing number of disabled elements. With multiple disabled elements, decreases in the detected maximum and average velocities greater than 20% were recorded. Similar results were also observed with Color Flow Doppler measurements. Our results confirmed that the degradation of the ultrasound probe through the loss of viable elements will negatively affect the quality of the Doppler-derived diagnostic information. We conclude that the results of Doppler measurements cannot be considered accurate or reliable if there are four or more contiguous dead elements in any given probe.
Keywords: Equipment Design; analýza selhání vybavení; ultrasonografie dopplerovská barevná; probe failure; ultrasonografie dopplerovská; dead elements; Reproducibility of Results; fantomy radiodiagnostické; Equipment Failure; Sensitivity and Specificity; senzitivita a specificita; Equipment Failure Analysis; reprodukovatelnost výsledků; flow test object; Ultrasonography, Doppler, Color; Doppler measurements; Phantoms, Imaging; quality assurance; design vybavení; Ultrasonography, Doppler; selhání zařízení